Low Dielectric Behavior of a Robust, Guest‐Free Magnesium(II)–Organic Framework: A Potential Application of an Alkaline‐Earth Metal Compound. Issue 10 (April 2015) - Mendiratta, Shruti; Usman, Muhammad; Tseng, Tien‐Wen; Luo, Tzuoo‐Tsair; Lee, Shang‐Fan; Zhao, Li; Wu, Maw‐Kuen; Lee, Mandy M.; Sun, Shih‐Sheng; Lin, Ying‐Chih; Lu, Kuang‐Lieh
Abstract: Invited for the cover of this issue is the group of Kuang‐Lieh Lu from the Institute of Chemistry, Academia Sinica, Taipei, Taiwan. The cover image shows the development of a robust, low‐ κ Mg MOF, representing a significant route for potential applications of Mg‐based MOFs as new interlayer dielectric materials. Abstract : The most exciting feature of this work is that the material reported in this paper has the lowest dielectric constant among all previously reported Mg‐based MOFs... Read more about the story behind the cover in the Cover Profile and about the research itself onp. 1669 ff .